Nourishing Newborns: Feeding Strategies to Minimize Allergy Risk in Preterm Infants - Faxriddinovna, Murtazayeva Zilola (American Journal of Bioscience and Clinical Integrity, 2024)
Preterm infants are a vulnerable population with an increased risk of developing allergic diseases. The type of nutrition they receive in early life plays a crucial role in shaping their immune system and influencing their susceptibility to allergies. This article reviews the current understanding of allergic diseases in preterm infants, focusing on the impact of different feeding methods, including breastfeeding, hydrolyzed protein formulas, and amino acid-based formulas.